The acylphloroglucinols hyperforin and myrtucommulone A cause mitochondrial dysfunctions in leukemic cells by direct interference with mitochondria - Wiechmann, Katja; Mueller, Hans; Fischer, Dagmar; Jauch, Johann; Werz, Oliver (Apoptosis, 2015)
The acylphloroglucinols hyperforin (Hypf) and myrtucommulone A (MC A) induce death of cancer cells by triggering the intrinsic/mitochondrial pathway of apoptosis, accompanied by a loss of the mitochondrial membrane potential and release of cytochrome c. However, the upstream targets and mechanisms leading to these mitochondrial events in cancer cells remain elusive. Here we show that Hypf and MC A directly act on mitochondria derived from human leukemic HL-60 cells and thus, disrupt mitochondrial functions. In isolated mitochondria, Hypf and MC A efficiently impaired mitochondrial viability (EC50 = 0.2 and 0.9 μM, respectively), caused loss of the mitochondrial membrane potential (at 0.03 and 0.1 μM, respectively), and suppressed mitochondrial ATP synthesis (IC50 = 0.2 and 0.5 μM, respectively). Consequently, the compounds activated the adenosine monophosphate-activated protein kinase (AMPK) in HL-60 cells, a cellular energy sensor involved in apoptosis of cancer cells. Side by side comparison with the protonophore CCCP and the ATP synthase inhibitor oligomycin suggest that Hypf and MC A act as protonophores that primarily dissipate the mitochondrial membrane potential by direct interaction with the mitochondrial membrane. Together, Hypf and MC A abolish the mitochondrial proton motive force that on one hand impairs mitochondrial viability and on the other cause activation of AMPK due to lowered ATP levels which may further facilitate the intrinsic mitochondrial pathway of apoptosis.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Apoptosis; Hyperforin; Leukemia; Mitochondria; Myrtucommulone